1981
DOI: 10.1111/j.1432-1033.1981.tb05078.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Links between Electron Transfer and Proton Translocation in Mitochondria

Abstract: The mechanism by which proton extrusion is linked to electron transfer in mitochondria was investigated by means of the primary amine-specific reagent fluorescamine, and of compounds obtained from the reaction of fluorescamine with simple amines (e.g. benzylamine) and with the mycosamine-containing antibiotic amphotericin B. The effect of these 'modifiers' (i.e. fluorescamine and the acyclic amine-fluorescamine compounds) on the activities of sites I1 and I11 of the electron transfer chain were assayed separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
6
0

Year Published

1981
1981
1990
1990

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 18 publications
3
6
0
Order By: Relevance
“…However, using a detailed kinetic model for the proton movement, we found that certain treatments did not change the H+ leakage of the membrane but yielded differential effects on the coupled activities in highly purified tonoplast membrane vesicles (27,28). This result suggested that the coupling between proton pumping and ATP hydrolysis may be indirect, as proposed earlier (25).…”
supporting
confidence: 55%
“…However, using a detailed kinetic model for the proton movement, we found that certain treatments did not change the H+ leakage of the membrane but yielded differential effects on the coupled activities in highly purified tonoplast membrane vesicles (27,28). This result suggested that the coupling between proton pumping and ATP hydrolysis may be indirect, as proposed earlier (25).…”
supporting
confidence: 55%
“…A similar preferential inhibition of proton pumping was also observed in the presence of acyclic (compound II) but not cyclic derivatives (compound III) (28). Thus, the presence of H-bond forming groups in the membrane was essential for inhibition.…”
supporting
confidence: 51%
“…The direct coupling mechanism implies that at least one molecular event must be common to the pathways leading to ATP hydrolysis and proton pumping (14). Coupling could also be accomplished through an indirect linkage, such as a membrane Bohr effect advocated by some researchers (10,28). In our previous work with corn root tonoplast vesicles, we demonstrated that proton pumping exhibited a greater sensitivity to nitrate inhibition (29), temperature (27), mercury (27), and divalent cations (30), as compared to ATP hydrolysis.…”
mentioning
confidence: 99%
See 2 more Smart Citations